2011
DOI: 10.1097/mcc.0b013e3283447759
|View full text |Cite
|
Sign up to set email alerts
|

Management of postcardiac arrest myocardial dysfunction

Abstract: Every community should be striving to provide more timely restoration of pulse and circulation, whereas every medical center receiving patients resuscitated from out-of-hospital cardiac arrest should be providing therapeutic hypothermia for both central nervous system and myocardial preservation. The ability and commitment to provide '24/7' early coronary angiography and percutaneous intervention for all resuscitated victims of sudden cardiac death with a likely cardiac cause for their arrest is also key.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…3). Using a post hoc Bonferroni correction, heart rates were independently lower in patients with favorable neurologic outcome at different time points post-ROSC compared with patients with unfavorable outcome (mean differences: 8 hr: 11; 95% CI, 4-18; 12 hr: 8; 95% CI, 1-14; 16 hr: 8; 95% CI, 3-14; 20 hr: 12; 95% CI, 6-18; 24 hr: 9; 95% CI, [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…3). Using a post hoc Bonferroni correction, heart rates were independently lower in patients with favorable neurologic outcome at different time points post-ROSC compared with patients with unfavorable outcome (mean differences: 8 hr: 11; 95% CI, 4-18; 12 hr: 8; 95% CI, 1-14; 16 hr: 8; 95% CI, 3-14; 20 hr: 12; 95% CI, 6-18; 24 hr: 9; 95% CI, [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 97%
“…Postresuscitation diastolic dysfunction has been shown to have a negative effect of hemodynamics in experimental (9) and clinical studies (10). Recent experimental studies have shown that TH may increase contractility, but further worsen diastolic dysfunction by increasing myofilament calcium sensitivity and diastolic tension as well as the systolic time of the contraction cycle (11).…”
Section: Discussionmentioning
confidence: 98%
“…This syndrome is characterized by cardiovascular instability and neurological injury resulting in a survival rate of 10% for out of hospital cardiac arrest (3). Global ischemia-reperfusion (IR) injury of the myocardium during cardiac arrest resuscitation is a known contributor to post cardiac arrest myocardial dysfunction and a likely contributor to the failure to achieve ROSC (3, 4). Mild hypothermia attenuates IR injury in cellular and animal models of cardiac arrest (57) and is now used clinically to improve human survival and neurological outcomes (8, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs have been tested to protect the myocardium from stunning and related injury, but with mixed clinical outcomes (5). Targeted temperature management using active cooling improves long-term neurologically-intact survival following CA (68) and has been proposed to aid cardiac recovery as well. In laboratory studies, cooling reduces cell death following myocardial ischemia (9) by activating Akt and Erk1/2, which are both members of the reperfusion injury salvage kinase pathway (10, 11).…”
Section: Introductionmentioning
confidence: 99%